The study of the lining layer abrasing wear in the semiautogenous grinding mill - Sokur, M.; Biletskyi, V. S.; Fyk, M. I.; Fyk, O.; Zaselskiy, I. (My University, 2020)
In this work complex investigations of the abrasing wear of lining of self-grinding mills (semiautogenous grinding mills) are carried out with the obtaining of mathematical models of wear-abrasing of elevators in terms of height, weight, volume and worn-out area. In particular, according to the location and nature of the abrasing wear processes, the liner-lifters mill self-grinding are identified in three typical groups. During 1 year, in the conditions of Ingulets GOK, the monitoring of the abrasing wear of selected groups of lifters of self-grinding mills was performed. On the basis of the experimental data calculationed in the Microsoft Office Excel program, a set of mathematical models of lifter abrasing wear was obtained in terms of height, weight, volume and worn-out area. The obtained dependencies are recommended for prediction of abrasing wear of lining and necessary frequency of replacement of inserts-lifters. In addition, the research of wear of lining made of cast iron RF–4, showed a significant reduction in their abrasing wear compared with steel 110G13L. Thus, it has been shown that the selection of liner-lifters materials can reduce the inter–repair period by 3 times or more (replacement of worn-out lifters). A comparison of the actual picture of the abrasing wear of elevators and Simulation Statics simulated result (using SolidWorks) stresses shows the convergence of the arrangement of the zones of maximum stresses and the maximum abrasing wear of the lining. Investigation of the influence of the stressed state of lining plates on the intensity of their abrasing wear – a promising direction for further research.
Keywords: abrasing wear; self-grinding mills; mathematical models; steel 110G13L; stressed state; lining plates